Large radio arrays for the detection of cosmic particles - Nelles, Anna (2021 34th General Assembly and Scientific Symposium of the International Union of Radio Science, URSI GASS 2021, 2021)
Recent years have shown a flurry of results from the radio detection of cosmic rays, both from dedicated arrays and from measurements using astronomical radio arrays. Detecting the radio emission from cosmic rays as messengers from the ultra-high energy universe has established itself as 'standard detection' method. Based on these successes the radio detection of similarly high-energy neutrinos is gaining traction. I will review the current status of the radio detection in the field of astroparticle physics, highlight future experimental efforts and elaborate on open questions and future experimental challenges.
CRIS-Team Scopus Importer:2021-11-12